(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2019)
The present work reports the extraction behaviors of mineral acids: HClO4, HNO3, HCl and H2SO4 (commonly found in acidic bleed solutions from the hydrometallurgical route of metal extraction processes) by tri-n-octylamine (TOA) dissolved in distilled colorless kerosene. The systems have been investigated as functions of various experimental parameters, such as time, [acid], [TOA], temperature, extraction stage and the organic to aqueous phase volume ratio (O/A). Strippings was also examined. Equilibration time is less than 60 min. The acid concentration in the organic phase at equilibrium is increased with increasing initial acid concentration in the aqueous phase for all systems. However, the is after %extraction decreased with increasing initial acid concentration in the aqueous phase. The % extraction increased remarkably with increasing [TOA] for all cases. Being the ratio of the [acid] in the organic to aqueous phase at equilibrium equal to extraction ratio, D; the log D vs. log [TOA] plot is almost a curve with slope 1 at lower concentration region and with slope 2 at higher concentration region. The extraction efficiency of TOA varies in the order: HClO4> HNO3> HCl > H2SO4. The acid-base-neutralization (extraction) reactions are exothermic with ΔH value much higher than -57 kJ/mol obtainable for of a strong acid - strong base neutralization. The loading capacity of extractant (g per 100 g TOA) for acids varied in the order: HClO4 (30.69) > HNO3 (20.49) > H2SO4 (17.87) > HCl (10.31). On using lower organic to aqueous phase volume ratio (O/A), the organic phase saturated with acid can be obtained on stage-wise extraction. The extracted organic phase, for all systems (excepting H2SO4-system) under investigation, can be stripped effectively in a single stage by 0.10 g eq/L NaOH solution to the extents of more than 96%. However, for H2SO4-system, two-stage stripping will be found effective. Bangladesh J. Sci. Ind. Res.54(4), 339-346, 2019